Influence of molecular weight on the morphology and structure of Electrospun Polyvinylidene Fluoride (PVDF) - Aminatul Sobirah, Zahari; Muhammad Hafiz, Mazwir; Izan Izwan, Misnon (Trans Tech Publications Ltd, Switzerland, 2021)
Polyvinylidene fluoride (PVDF) reveals outstanding properties such as lightweight, high flexibility and temperature independence material compared to other polymers. In this study, PVDF as a function of molecular weight was prepared by using an electrospinning method in order to study the influences of the molecular weight of the PVDF membrane on the morphology. Analytical techniques such as field emission scanning electron microscope (FESEM), Fourier transform infrared (FTIR) and X-ray diffraction (XRD) were used to characterize the electrospun PVDF membranes. FESEM was used for morphology characterization and also to measure the diameter of fibers while XRD and FTIR were employed to examine crystalline phase membranes. The lowest molecular weight has the smallest average diameter of fibers. Besides, a combination of both α-phase and β- phase crystalline was showed by XRD and FTIR results. This is because the crystalline phases and membrane morphology depend on the polymer molecular weight. In this research, it was found that the largest β-phase fraction for the electrospun PVDF membrane is 80.25 % with a molecular weight at 180,000 g/mol.